Itogi . Itogi . Results . Итоги - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Boris Yeltsin's visit to Britain; the Congress of Russian Industrialists and Entrepreneurs; the views of party leaders on the political situation in Russia; the use of vouchers; the Chechen conflict; Day of Army Draft in Russia; an increase in the exchange rate of the US dollar; coverage on the problems of the Siberian Branch of the Russian Academy of Sciences; interview with Jimmy Carter. Featured in the program: Carter, Jimmy (President of the United States) Contributors: Kiselev, Evgenii (Anchor) Series description: Weekly information and analytical program hosted by Evgenii Kiselyov. Broadcasted from January 3, 1992 till June 15, 2003. The program discussed and analyzed major political news and regularly invited to the show prominent politicians, public and cultural figures. Визит Бориса Ельцина в Великобританию; съезд российских промышленников и предпринимателей; политическая ситуация в России по мнению лидеров партий; использование ваучеров; чеченский конфликт; День призывника в России; рост курса доллара; репортаж о проблемах работы Сибирского отделения Российской академии наук; интервью с Джими Картером. В программе участвуют: Картер, Джимми (Президент США) Создатели: Киселев, Евгений (Ведущий/Ведущая) Описание серии: Еженедельная авторская информационно-аналитическая передача Евгения Киселёва, выходившая с 3 января 1992 по 15 июня 2003 года. В программе обсуждались и анализировались главные политические новости, события и тенденции политической жизни, регулярно выступали известные политики, общественные и культурные деятели.